The Influence of Lifestyle, Brand Image and Word of Mouth on Purchasing Decisions of Oppo Brand Cellphones on Mamuju Muhammadiyah University Students - Kamarudin, Jamaludin; Ferils, M. Bachri, Muh. ? (Program Pascasarjana STIE Amkop Makassar, 2023)
Penelitian ini menguji dampak gabungan dan individu dari